KEMATANGAN JIWA BERAGAMA - Mulyono, Mulyono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Human beings have two experiences; a) physical, and b) spiritual. The physical growth is based on the chronological age, then that is known as adultery. Whereas the spiritual growth is based on the capability level, and the top of this growth is known as maturity. The growth level that is achieved by every individual will be different. Anyone can be adult physically, not spiritually. To be adult spiritually, someone may be mature in his/her personality soul. The people's soul is mature when the people's mature soul is interrelated with religiosity that is known as a maturity of religious soul. 17zere are six characteristics of maturity: 1) having a good differentiation, 2) having dynamic motivation in spiritual life, 3) having proper implementation of the religion consistently and productively, 4) having comprehensive point of view, 5) having integrated point of view and 6) having high motivation in finding and serving the God.